Colour and Meaning in Corporate Logos: An Empirical Study - Hynes, Niki (Palgrave Macmillan, 2009)
Corporate visual identity helps establish and maintain a company ’ s corporate image, of which thecolour and design of a company ’ s logo is central. This study examines the triadic relationshipbetween colour, design and the evoked meanings of logos to understand how these contribute tobuilding a consistent corporate image. Results strongly indicate that consumers make clearjudgements about the image of a fi rm from the logo design and have strong opinions about whichcolours are appropriate for different corporate images.